Gestão democrática e participação na educação profissional agroecológica do MST (PR) limites e possibilidades de uma educação emancipatória - Lima, Laís Ribeiro dos Santos (Editora Oficina Universitária, 2020)
The dominant mode of production relations, between men and nature, and among themselves, if they are not exhausted, are at the insurmountable limit of their potential. Forces of social development in the past, these relationships have become their antithesis, an immense social problem that claims to be overcome historically. As the owners of power are inexorably committed to the social order, the task falls to the working classes, who rely on a secular teleology of social revolution. A fragment of this teleology, protosocialist, was what Laís Lima came across in her historical-empirical study carried out at the Milton Santos School, in Maringá, PR. The researcher found that it practices a pedagogy opposed to the aforementioned antinomies, and that its main tools are the teaching of agroecology and democratic management. Agroecology promotes a non-aggressive relationship between society and nature, as well as the understanding that its practice is incompatible with dominant work relationships. This is one of the reasons why its increase is inseparable from the establishment of new pedagogical production relations. These are expressed in the democratic management of the school, whose kinship, however, is not liberal democracy, but the proletarian democracy that emerged in the Paris Commune. Lima's excellent work leads us safely through the intricacies of this school practice, which facilitates consultation by readers, among which the popular movement (MOP) is virtually the most interested. This is because the examined phenomenon is a suggestive example of how, mutatis mutandis, the much-needed reunion of the MOP with the classic objective of reappropriation of work by workers, which, in the Anthropocene, cannot do without the struggle for agroecology.